Ph̄æn phatthanā Čhangwat Chaiyaphūm 4 pī (Ph̨̄o.S̨̄o. 2552 - 2555) (Klum Ngān Yutthasāt Kānphatthanā Čhangwat, Samnakngān Čhangwat Chaiyaphūm, 2008)
On four-year development plan of Chaiyaphum province, northeastern Thailand.